Peran Mahkamah Konstitusi dalam Mempertahankan Negara Hukum dan Mengupayakan Perlindungan Hak Asasi Manusia - Nurul Syafriyani; Dwi Febri Susilawati; Kevin Rivaldi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The Constitutional Court (MK) of the Republic of Indonesia plays a vital role in upholding the principles of the rule of law and the protection of human rights (HAM). MK operates through the judicial review mechanism to ensure that laws in force do not contradict the 1945 Constitution. Additionally, MK oversees the legislative process, ensuring transparency and public participation. In human rights protection, MK cancels provisions of laws that violate fundamental rights, with significant decisions related to freedom of expression, freedom of religion, and children's rights. MK also protects economic, social, and cultural rights, ensuring equal access for all citizens. Despite facing challenges such as political pressure and legal complexity, MK maintains its integrity through transparency and accountability. Overall, MK ensures that Indonesia remains a democratic and just state governed by the rule of law.